6z+15=6(z+4)-14

Simple and best practice solution for 6z+15=6(z+4)-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6z+15=6(z+4)-14 equation:


Simplifying
6z + 15 = 6(z + 4) + -14

Reorder the terms:
15 + 6z = 6(z + 4) + -14

Reorder the terms:
15 + 6z = 6(4 + z) + -14
15 + 6z = (4 * 6 + z * 6) + -14
15 + 6z = (24 + 6z) + -14

Reorder the terms:
15 + 6z = 24 + -14 + 6z

Combine like terms: 24 + -14 = 10
15 + 6z = 10 + 6z

Add '-6z' to each side of the equation.
15 + 6z + -6z = 10 + 6z + -6z

Combine like terms: 6z + -6z = 0
15 + 0 = 10 + 6z + -6z
15 = 10 + 6z + -6z

Combine like terms: 6z + -6z = 0
15 = 10 + 0
15 = 10

Solving
15 = 10

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -5x-1.5+8=2.5-1x | | 2v+29=9(v+9) | | x^2-25x+150= | | 6x+0.3= | | 3x-2.5+4=4.5+x | | -42=-7 | | 118x=1/3 | | 46+7.3g=46.0365 | | 5(4x-7)=-21(5-x) | | 1/3x=118 | | (8h-1)-(h+3)h=-3 | | y=(2x-1)/(4) | | 5/6(6t-6)-3 | | 2(96+l)+2(60+w)= | | -7u+5(u-2)=-14 | | 118x=2/3 | | 3b+14=11 | | pq=y | | 6x+8x-5=23 | | Lnx-7=-3.2 | | 2x+36y=-1 | | 1=2n-n | | 12x+1=3(4x+1) | | 6(d+9)=90 | | y=2x-1/4 | | k/3-3=4 | | Q/4-1=5 | | 2x-4+0.2+0.3=7 | | X+6.2=9.1 | | 11f-(-2f+2)f=.5 | | X^2-2x+x-2=54 | | 1/2y=x=6 |

Equations solver categories